Revictimization: towards a new theoretical concept - Gopalan, Rejani Thudalikunnil (Victimology, 2022)
Many studies have shown that being a victim of an assault or crime increases the chance of revictimization, and the current chapter deals with this aspect of victimization. The concept of revictimization has been defined in many different ways but the common theme that arises is the repetition of the victimization of the same person, which can be physical, sexual, emotional, or any form of abuse. Studies showed that revictimization exists and it happens especially in sexual assault and intimate partner violence. Though these are the two distinctive forms of violence, some underlying features may be there as common core reasons for revictimization. This chapter explores the factors associated with the revictimization of sexual abuse and intimate partner violence (IPV) to delineate the common factors in both the violations. From the background of ecological and violence perspectives, and clinical and research experiences with different forms of violence and crimes, the author introduces a conceptual framework for revictimization. As it is a thread of conceptual formulation of theory, empirical studies are required to validate it.